The city between freedom and security. Contested public spaces in the 21st century. - (:unkn) unknown (Birkhäuser, 2017)
Das urbane Dilemma: den staatlichen Bestrebungen, den städtischen Raum sicherer zu machen, steht das Prinzip gegenüber, dass Städte ein Raum einer offenen Zivilgesellschaft und Demokratie mit Meinungs- und Versammlungsfreiheit sind. Wie lassen sich beide Interessen in eine Balance bringen? Ausgehend von der viel diskutierten Sanierung des Regierungsviertels in Oslo nach den Anschlägen von 2011, bietet das Buch eine breite Diskussionsplattform für die unterschiedlichen Positionen an der Schnittstelle zwischen Architektur/Urbanismus und Sicherheit/Demokratie.

This publication explores the contested territory between the state and corporate drive to 'securitise' urban space - and the principle of the city as a site for enacting open civil society, participatory democracy, and the freedom of speech and assembly. Starting from the disputed redevelopment of the Oslo Government Quarter since its attack in 2011, the book functions as a broader discursive platform mediating opposing positions at the intersection of architecture/urbanism and security/democracy. The book interposes essays, interviews, site drawings, a lexicon of terms, and photo-essays documenting fieldwork in the UK, USA, Israel, Palestine and Spain. Contributors include: S. Graham, M. Sorkin, D.Harvey, G. Agamben, Y. Yasky, L. Lambert, CPNI, R. V. Clarke, J. Coaffee, and O. Newman.
Keywords: Stadtplanung; Öffentliche Sicherheit; Stadtraum; Öffentlicher Raum; Nutzungskonflikt; Nutzungseinschränkung; Zivilgesellschaft; Versammlungsfreiheit; Kontrolle